2020
DOI: 10.3390/su12104286
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Environmental Advisory Councils: How They Work and Why it Matters

Abstract: In many countries, advisory councils are the most common participatory institution in which public administration interacts with civil society around environmental issues. Nevertheless, our knowledge about them is quite limited. The main goal of this article is to show the differences they present with advisory councils in other policy areas in three main aspects: who participates, how they work, and which are their outputs. These differences are especially important because they emerge again regarding their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…Sus integrantes valoraron positivamente, sobre todo, la dimensión inclusividad. El balance sobre los medioambientales resulta negativo, en sintonía con investigaciones previas (Alarcón et al, 2020). Pese a que alguno (sobre todos, destaca el Consejo para la Protección de la Naturaleza de Aragón, véase tabla 4) aparece entre los mejor puntuados, observamos un panorama general en el que los esfuerzos en diseño parecen orientarse al aspecto informativo (otorgan importancia a la presencia de expertos), quedando desprovistos aspectos clave como la inclusividad y la transparencia.…”
Section: Conclusionesunclassified
“…Sus integrantes valoraron positivamente, sobre todo, la dimensión inclusividad. El balance sobre los medioambientales resulta negativo, en sintonía con investigaciones previas (Alarcón et al, 2020). Pese a que alguno (sobre todos, destaca el Consejo para la Protección de la Naturaleza de Aragón, véase tabla 4) aparece entre los mejor puntuados, observamos un panorama general en el que los esfuerzos en diseño parecen orientarse al aspecto informativo (otorgan importancia a la presencia de expertos), quedando desprovistos aspectos clave como la inclusividad y la transparencia.…”
Section: Conclusionesunclassified
“…Research about public opinion and policy-making has clearly established that not all policy areas are equally sensitive to citizen input. In the specific world of ACs, Pogrebinschi and Ryan (2017) established that the type of policy has a clear effect on their potential impact, and Alarcón et al (2020) show that environmental councils have a much larger degree of conflict.…”
Section: Do Territorial Scales Matter?mentioning
confidence: 99%
“…Apart from the previously referenced works, the following publications draw attention:Baker (2006) Van Damme et al (2011), Boss (2017), Frączkiewicz-Wronka et al (2019),Sant and Davies (2018),Schulte (1999),Wang (2001). Th e recent return to the research on ACs can be particularly observed in works ofAlarcón et al (2020),Brugué et al (2020),Galais et al (2020),,.…”
mentioning
confidence: 99%